Patterns of leisure participation among older people and their health conditions: a survey in Fujian, China - Li, Zhen; Yan, Xiao (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to explore the association between leisure activity participation and health conditions among older adults in Fujian Province, China.MethodsThis is a population-based cross-sectional study including a multiple-stage sample of 527 subjects aged 60 years and older. Physical activity was evaluated using the long version of a questionnaire designed to assess the living conditions of Chinese older adults in urban and rural areas, using home interviews with a last-week recall. The questionnaire includes 14 different activities, which are grouped into 5 activity types.ResultsNearly 20% of the subjects participated in one or fewer leisure activities, and the young-old subjects and men were more likely to engage in vigorous activities than their counterparts. Older adults who had better self-rated health enjoyed more leisure activities than those who rated themselves in poor health after controlling for some demographic factors. Participants living in urban areas with better self-rated health and higher educational levels showed more participation in mental, physical, and productive activities.ConclusionThe findings identify significant correlates of leisure activity participation among older Chinese adults, providing preliminary evidence to support the development of successful aging initiatives and health policies for older populations.